Innovative strategies for sustainable campus management: Insights from "Karya Hijauku untuk Kampus Biruku” - Mochamad Arief Rizki Mauladi; Malinda Aptika Rachmah; Fasya Fauziah Sodik Binti Nasr (Interdisciplinary International Journal of Conservation and Culture, 2025)
"Karya Hijauku untuk Kampus Biruku" describes the strategic efforts of Universitas Gadjah Mada (UGM) in managing natural resources and implementing the green campus concept. This book discusses in detail land use, water resource management, and waste management in the campus environment. This article reviews the book with a focus on the relevance of natural resource conservation efforts  kk jaya furniture implemented by UGM. The review involves analyzing the book's strategies, challenges, and contributions to the literature on environmental conservation. This book is an inspiration and practical guide in creating an environmentally friendly, sustainable campus.